Life-Cycle and Altruistic Theories of Saving with Lifetime Uncertainty - Kuehlwein, Michael (The Review of Economics and Statistics, 1993)
This paper examines testable implications of the life-cycle theory of saving with lifetime uncertainty. Theory sugges ts that persons facing lower mortality rates should exhibit greater consumption growth. Nonparametric tests, using the Retirement Histor y Survey, provide mixed support for the theory. A parameterized model allowing for altruism provides more support. Estimates of a bequest parameter indicate that elderly households value contributions to bequests as highly as contributions to their own consumption. This i s equally true for households with and without children. Such a beques t motive would curtail the impact of lifetime uncertainty on consumpti on growth. Copyright 1993 by MIT Press.